Hydrochemical assessment of the quality of thermal mineral water for irrigation - Benamara, Abdelwaheb (Acta hydrotechnica, 2022)
This study was carried out to assess the state and quality of Hammam Meskoutine's thermal mineral water and its suitability for irrigation. To accomplish this, water samples from ten different thermal mineral springs were evaluated in February and June of 2016, respectively, in the region of Hammam Meskoutine in northeastern Algeria. The analyzed parameters are the water’s physical and chemical characteristics (temperature, pH and electrical conductivity) as measured in situ, and the dosing of the major components (Cl- , SO42- , HCO3 - , Ca2+ , Mg2+, Na+ , and K+ ) in the laboratory. Based on the chemical analyses, irrigation quality parameters were calculated, e.g. the sodium absorption ratio (SAR), the percent of sodium (% Na), residual sodium carbonate (RSC), permeability index (PI), and magnesium hazard (MH). The results showed the spring water there to be generally unsuitable for irrigation practices during the two sampling periods.
Keywords: Hammam Meskoutine; irrigation; kakovost vode; namakanje; preostali natrijev karbonat; razmerje adsorpcije natrija; residual sodium carbonate; sodium absorption ratio; termomineralna voda; thermal mineral water; water quality